2020
DOI: 10.1177/2329496520959297
|View full text |Cite
|
Sign up to set email alerts
|

No Justice, No Peace? Protest Participation for People with Criminal Legal Contact

Abstract: Previous research shows that people who have criminal legal (CL) contact are less likely to vote, but there is little information about whether or not CL contact influences protest participation. While people with CL contact may be more likely to engage in critiques of the state, they are also more vulnerable to the risks associated with protesting. Because the CL system is highly racialized in the United States, race is central to an analysis of CL contact. In this article, I analyze the relationship between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 88 publications
0
3
0
Order By: Relevance
“…Scholars have also suggested that one’s social position and culture can be driving factors for participation in protests (Armstrong & Bernstein, 2008; Van Stekelenburg & Klandermans, 2013). For example, in her investigation of the relationship between criminal legal contact and protest participation, Eife (2020) discovered that among those who had criminal legal contact perceived injustice influenced their participation in protests, especially for Black individuals. Black people who had contact with the criminal legal system were more likely to participate in protests over both non-Blacks who had criminal legal contact and Blacks without criminal legal contact.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Scholars have also suggested that one’s social position and culture can be driving factors for participation in protests (Armstrong & Bernstein, 2008; Van Stekelenburg & Klandermans, 2013). For example, in her investigation of the relationship between criminal legal contact and protest participation, Eife (2020) discovered that among those who had criminal legal contact perceived injustice influenced their participation in protests, especially for Black individuals. Black people who had contact with the criminal legal system were more likely to participate in protests over both non-Blacks who had criminal legal contact and Blacks without criminal legal contact.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Black people who had contact with the criminal legal system were more likely to participate in protests over both non-Blacks who had criminal legal contact and Blacks without criminal legal contact. These elements combined with formal and informal network ties, media consumption, moral conflict, level of motivation, and organizational participation assist in the recruitment and mobilization processes of social action (Eife, 2020; McAdam & Paulsen, 1993; Passy & Guingi, 2001; Van Stekelenburg & Klandermans, 2013). Level of commitment to the cause also is an important factor for protest engagement.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Second sight also constitutes behaviors-not just attitudes-that may be unique. For instance, Erin Eife (2020) shows that Black people with criminal legal system contact are more likely to report participating in protests than both Black people without such contact as well as non-Black people with contact, suggesting that perceived racism may impact second sight among the criminalized (see also Cobbina 2019). Criminalized people's experiences could contribute novel visions about how the system and broader society could be changed to better incorporate, forgive, and heal the criminalized.…”
Section: A Du Boisian Theory Of Criminalized Subjectivity and Legal Envisioningmentioning
confidence: 99%